(3eNJUQ JfHjg GdWGdH hEQTGO GdOGQS aje aj OeTb ef GdLhGeY hGdeOGQSs - (3GdYdehis; (3GdfYjej , YHO GdbGOQ Hf eMeO Hf YeQ Hf eMeO Hf jhSa HfYHO Gddg Hf fYje, CHh GdeaGNQ,J (B927 (3g` s
(3ChdgG (B:s
(3Chd eGajg cdGe Yf OGQ GdbQBf GdOdGejI s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B43 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B301s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B164 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B264 s
Keywords: (3GdJGQjNs